SUPPLEMENTATION OF VITAMIN E AND C IN FEED ON MEAT QUALITY, THIOBARBITURIC ACID REACTIVE SUBSTANCE (TBARS) AND MYOGLOBIN LEVEL OF MUSCOVY DUCK MEAT - Tugiyanti, E.; Yuwanta, T.; Zuprizal, Zuprizal; Rusman, Rusman (Diponegoro University, 2014)
This research was aimed to analyze vitamin E and C supplementation in feed on meet quality,thiobarbituric acid reactive substances (TBARS) and myoglobin level of muscovy duck. This researchused 84 Indonesian muscovy duck divided into 7 group of experimental diet, namely E0C0 : basal feedwithout vitamin E and C supplementation, E400 : basal feed with 400 IU of vitamin E supplementation,E600 : basal feed with 600 IU of vitamin E supplementation, C400 : basal feed with 400mg vof itamin Csupplementation, C600 : basal feed with 600mg of vitamin C supplementation, E200C200 : basal with 200 IUof vitamin E and 200mg of vitamin C supplementation, E300C300 : basal feed with 300 IU of vitamin Eand 300mg of vitamin C. A completely randomized design was applied and each treatment had 4replications. The data were analyzed using analysis of variance. Analysis of variance showed thattreatments significantly affect (P>0.01) meat quality, myoglobin level and TBARS level. Vitamin E andC was proven able to improve final pH of muscovy duck meat. Supplementation of 300 IU of vitamin Eand 300mg of vitamin C at feed with 21% of protein and 3100 kcal/kg of energy could improve DIA,cooking loss, flavor, and color of muscovy duck meat; however, the highest meat tenderness wasresulted from 400 IU vitamin E supplementation.